Stress and cognitive functioning in sport - Jones, J. G.; Hardy, L. (Journal of Sports Sciences, 1989)
This paper considered the relationships between stress, cognitive functioning, and sports performance: - Unidimensional Models - Multidimensional Models of Stress and Performance . Anxiety-based models of stress . Multidimenionsal activation states . Stress effects upon energetical and structural components of performance. Summary Unidimensional models of the stress-performance relationship are too limited to be of value for understanding sporting performances. Their purely mechanical (physiological) basis is too restrictive. Without strong considerations of cognitive factors in the response, prediction will be very weak. 1.The notion of one general arousal system is insufficient to explain stress effects upon performance. 2.Competitive state anxiety is multidimensional comprising cognitive anxiety, somatic anxiety, and self-confidence. This requires specific interpretations of situations and the nature of an athlete's response. 3.Stress effects are situation-specific. 4.Stress effects are task-specific. They are dependent upon the cognitive requirements of the task so that different task components can be affected in different ways by the same stressor. 5.Stress effects are individual- and individual-by-situation-specific. Cognitive skills and past histories of experiences will play a large role in defining the uniqueness of responses. The relationship between stress and sports performance is an extremely complex one that involves an interaction between the nature of the stressor, the cognitive demands of the task, and psychological characteristics and abilities of the individual performing it. It is inappropriate to consider stress effects upon performance without considering the mental states brought to the scene and the cognitive activities that occur in the situation.